Implementation of tumor-free and total Müllerian compartment resection techniques in robot-assisted radical hysterectomy: protocol for standardizing surgical procedures - Wang, Xinyou; Zhu, Jinming; Li, Siman; Na, Jing; Wang, Jun; Han, Shichao; Li, Ya (Frontiers in Oncology, 2025)
ObjectiveThe main objective of this study is to apply the tumor-free technique in robot-assisted radical hysterectomy to effectively prevent tumor exposure and dissemination during the operation. Meanwhile, this study aims to standardize and optimize this technique, thereby promoting its wide application in clinical practice and ensuring the stability and reproducibility of surgical outcomes.MethodThe surgical indications for this study were as follows: patients with stage IA2, IB1, IB2, IIA1, and certain specific pathological types of IB3 and IIA2 cervical cancer(FIGO 2018). During the operation, suture suspension of the uterus was used instead of a uterine manipulator. Before incising the vagina, the vaginal orifice was closed. After completing the vaginal closure, the vaginal wall was rinsed with 42°C sterile distilled water. All surgical procedures followed the concept of embryonic compartment-based hysterectomy according to membrane anatomy, ensuring the integrity of the Müllerian embryonic compartment’s membrane structure.ResultsGuided by the concept of membrane anatomy, robot-assisted radical hysterectomy facilitates bloodless surgery while improving surgical efficiency and precision through the simplification and optimization of techniques. Moreover, this approach maintains the integrity of the Müllerian duct embryonic compartment, thus preventing tumor spillage. When integrated with tumor-free exposure techniques, it offers cervical cancer patients the advantages of minimally invasive surgery, including faster recovery, reduced surgical trauma, and a lower risk of iatrogenic tumor dissemination.ConclusionEmploying robotic technology in conjunction with the concept of membrane anatomy during radical hysterectomy can lead to a more meticulous and precise surgical outcome. The application of precise surgical techniques not only facilitates the standardization and optimization of procedures but also minimizes patient trauma and accelerates recovery.